Change is Possible: A Case Study of Multicultural Education in Slovenia - Pliberšek, Urška (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2024)
This study investigated the attitudes of Slovene elementary school students towards multiculturalism and the effect of educational workshops on these attitudes. This research fills a gap in the existing literature as there is a lack of studies on the impact of multicultural workshops in Slovenia. This study employed a case study approach that focused on a specific elementary school. The literature review discusses the concept of multiculturalism, approaches to multicultural education, and attitudes of teachers and the general population towards multiculturalism. These findings suggest that children's attitudes towards multiculturalism can change over time if they are exposed to multicultural workshops and learn about multiculturalism. This study also highlights the lack of knowledge and experience among Slovene teachers regarding multicultural education. The results contribute to the understanding of multicultural education in the Slovenian context and provide insights into the effectiveness of educational workshops in shaping students' attitudes towards multiculturalism. This study has implications for educators and policymakers in designing and implementing multicultural education programmes in elementary schools.